Memorie e ferite storiche. Il caso de L’espulsione di Gerta Schnirch - Stefania Mella (Lea, 2014)
This article aims to explain the painful experience of Gerta, the protagonist of Kateřina Tučková’s novel Vyhnání Gerty Schnirch (The Expulsion of Gerta Schnirch). Her story develops through the years following World War II, when many Germans were forced to leave Czechoslovakia. Gerta, a young lady of Czech-German descent, is deeply affected by the expulsion and its aftermath. Her life will be branded for good by the multitude of harsh episodes which will be the cause for the protagonist of a slow, yet unavoidable decline. The historical events provide not only the background for the story, but also act as a violent, cruel machine that slowly consumes Gerta, leaving her empty and drained. With nothing else to lose and nothing else to fight for, a feeling of death grips the protagonist until it overwhelms her completely.